Biliary atresia in preterm infants: a single center experience and review of literature - Beati, Federico; Mosca, Antonella; Pietrobattista, Andrea; Liccardo, Daniela; Ronci, Sara; Monti, Lidia; Francalanci, Paola; Spada, Marco; Maggiore, Giuseppe; Bagolan, Pietro; Fusaro, Fabio (Frontiers in Surgery, 2024)
Introduction: Biliary atresia (BA) diagnosis is still challenging, and the optimal timing of Kasai portoenterostomy (KPE) remains unclear. Little is known on difficulties in diagnosis and on outcome of BA in preterm infants (PBA). Aim of this study is to describe a single-center experience on BA in preterm newborns; this represents the first Italian report. Methods: We retrospectively reviewed of all consecutive infants diagnosed with BA who underwent Kasai procedure between January 1998 and December 2021 at Bambino Gesù Children Hospital. Prematurity was defined as gestational age (GA) < 37 weeks. Demographic, laboratory, and histology data were recorded. Main outcome considered were clearance of jaundice (COJ), native liver survival and mortality. Results: 21 PBA were compared with 117 term BA controls (TBA). Median GA of PBA was 35,1 [32–36.1] weeks, birth weight was 2100 [1897-2800] g. Age at first presentation was significatively lower for PBA patients: 46 (22-68) vs 61 (44-72) days; p=0.02. Median age at KPE was similar between two groups: 70 days (33 corrected) for PBA vs. 67 in TBA; p=0.8. At the time of surgery, median serum bilirubin was lower for the PBA group (7.7 vs. 8.6 mg/dL, p = 0.04). Similarly, median APRi at the time of KPE was lower but not significant in the PBA cohort: 1.09 vs. 1.16; p=0.8. No differences were found in terms of clearance of jaundice (COJ) between PBA and TBA: [n=9 (43 %) vs 34 (35%), p=0.2]. Overall native liver survival was similar between the two groups: 8.6 (4.8-12.2) for PBA vs 7.6 (5.6- 9.5) years for TBA with no significant differences; p=0.45 (figure 3). Post-KPE native liver survival was similar between the two groups: 38% vs 52% at 5 years, for TBA and PBA, respectively; p= 0.54. Conclusion: PBA and TBA patients seem to have similar outcomes in terms of COJ, overall native liver survival and 5-years liver survival. Considering corrected gestational age, early KPE is related to lower cholestatic damage. Further multicenter studies are required.